Loneliness Abroad: The Role of Emotional Support of Boarding House Managers for Students - Zahra Vidya Putri; Any Nurhayaty; Tansri Adzlan Syah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Migrant students often experience loneliness due to separation from their families and familiar environments. This loneliness is not merely caused by the absence of social interaction but also by a lack of meaningful emotional support in the new setting. This study aims to examine the relationship between emotional support provided by boarding house managers and feelings of loneliness among migrant students. A quantitative method with a correlational design was used. The sample consisted of 210 migrant students living in boarding houses or dormitories, and data were collected using two instruments: an emotional support scale and a loneliness scale. Data were analyzed using the Spearman correlation test. The results indicate a significant negative relationship between emotional support from boarding house managers and the level of loneliness among students. This means that the higher the emotional support perceived from the boarding house managers, the lower the level of loneliness experienced by the students. Future research is encouraged to include mediating variables such as attachment or emotion regulation to further explore the underlying mechanisms of this relationship. The implication of this study highlights the importance of involving boarding house managers as informal agents of emotional support to foster a more supportive and psychologically healthy living environment for migrant students.Mahasiswa perantauan kerap mengalami kesepian akibat keterpisahan dari keluarga dan lingkungan asal. Kesepian ini tidak hanya disebabkan oleh ketiadaan interaksi sosial, melainkan juga oleh kurangnya dukungan emosional yang bermakna di lingkungan baru. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan emosional dari pengelola kost dengan perasaan kesepian pada mahasiswa perantauan. Metode yang digunakan adalah pendekatan kuantitatif dengan desain korelasional. Sampel terdiri dari 210 mahasiswa perantauan yang tinggal di kost atau asrama, dan data dikumpulkan menggunakan dua instrumen: skala dukungan emosional serta skala kesepian. Analisis data dilakukan menggunakan uji korelasi Spearman. Hasil penelitian menunjukkan bahwa terdapat hubungan negatif yang signifikan antara dukungan emosional dari pengelola kost dan tingkat kesepian mahasiswa perantauan. Hal ini berarti bahwa semakin tinggi dukungan emosional yang dirasakan dari pengelola kost, maka semakin rendah tingkat kesepian yang dialami mahasiswa. Penelitian ini menyarankan agar studi selanjutnya mengikutsertakan variabel mediasi seperti keterikatan atau regulasi emosi untuk memahami mekanisme hubungan lebih dalam. Implikasi dari penelitian ini menekankan pentingnya pelibatan pengelola kost sebagai agen dukungan emosional informal untuk menciptakan lingkungan tinggal yang lebih suportif dan sehat secara psikologis bagi mahasiswa perantauan.